The Thiamin-Requiring 3 Mutation of Arabidopsis 5-Deoxyxylulose-Phosphate Synthase 1 Highlights How the Thiamin Economy Impacts the Methylerythritol 4-Phosphate Pathway - Joshi, Jaya; Mimura, Manaki; Suzuki, Masaharu; Wu, Shan; Gregory, Jesse F.; Hanson, Andrew D.; McCarty, Donald R. (Frontiers in Plant Science, 2021)
The thiamin requiring mutants of Arabidopsis have a storied history as a foundational model for biochemical genetics in plants and have illuminated the central role of thiamin in metabolism. Recent integrative genetic and biochemical analyses of thiamin biosynthesis and utilization imply that leaf metabolism normally operates close to thiamin-limiting conditions. Thus, the mechan-isms that allocate thiamin diphosphate (ThDP) co-factor among the diverse thiamin dependent enzymes localized in plastids, mitochondria, peroxisomes, and the cytosol comprise an intricate thiamin economy. Here we show that the classical thiamine requiring 3 (th3) mutant is a point mutation in plastid localized 5-deoxyxylulose synthase (DXS1), a key regulated enzyme in the MEP isoprene biosynthesis pathway. Substitution of a lysine for a highly conserved glutamate residue (E323) located at the subunit interface of the homodimeric enzyme conditions a hypomorphic phenotype that can be rescued by supplying low concentrations of thiamin in the medium. Analysis of leaf thiamin vitamers showed that supplementing the medium with thiamin increased total ThDP content in both wild type and th3 mutant seedlings, supporting a hypothesis that the mutant DXS1 enzyme has a reduced affinity for the ThDP cofactor. An unexpected up-regulation of a suite of biotic-stress-response genes associated with accumulation of downstream MEP intermediate MEcPP suggests that th3 causes mis-regulation of DXS1 activity in thiamin-supplemented seedlings. Overall, these results highlight that the central role of ThDP availability in regulation of DXS1 activity and flux through the MEP pathway.